The roman legionary fortress at Tilurium - state of research - Sanader, Mirjana (Array, 2006)
The roman legionary fortress Tilurium is situated within the modern village of Gardun.From 1997 archaeological exavations were initiated at Tilurium. This exavations provided excellent results which are presented in this book.